PEMBELAJARAN KEWIRAUSAHAAN MELALUI KOLABORASI ANTARA SEKOLAH DENGAN DUNIA USAHA (DUNIA INDUSTRI) PADA SISWA SMK NEGERI 3 KUDUS TAHUN 2013 - Mustakim, Mustakim (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
Entrepreneurial learning associated with the learning outcomes of students in secondary vocational schools in order to produce graduates who are capable of self-employed and compete as experts in their respective fields according to the occupied during the study. Students of vocational high school graduates who are independent self-employed will be able to compete in the global era. Graduates will be influenced by the conditions of entrepreneurial learning in schools in cooperation with the business (industry) studied the learning process. Vocational industrial education that prepares a person to be more capable of working in a job group or field of work than the work are a sother. In SMK N 3 Kudus an educational institution that prepares students to be able to work independently in a particular field. World Business School and the implementation of education has an important role in the development of education in this regard are implemented in the learning process. Based on this background, it can be taken to focus the problem as follows: The process of entrepreneurial learning by the student of SMK N 3 Kudus in the classroom, practice and learning in the corporate world to entrepreneur ship students at SMK N 3 Kudus, The World of collaboration between schools and businesses (World Industries) in teaching entrepreneurship to students at SMK N 3 Kudus and the impact on students' entrepreneurial learning through collaboration between schools and business (industry) to knowledge (skill) competencies of entrepreneurship students at SMK N 3 Kudus.From the analysis it can be concluded that the impact of collaboration between the World of Business Schools in entrepreneurship learning in students SMKN 3 Kudus is able to develop the entrepreneurship spirit of students so as to enhance the spirit of independence of students in employment. As the end of the description of the study, the authors make suggestions as follows: for the teaching staff at secondary vocational schools, involvement in the learning of each should be able to insert material that related to entrepreneurship as a subject is part of the learning process of students to be able to gave the impetus to entrepreneurship in independent. Schools and businesses are a single entity in the process of learning in secondary vocational schools then both agencies should support each other for the success of education and training programs that have been outlined in the 1945 opening of the intellectual life of the nation and the entire homeland.Keyword: Enterpreunership’s, School, Effort The World (Industrial The World)Pembelajaran kewirausahaan terkait dengan hasil belajar siswa di sekolah menengah kejuruan untuk menghasilkan lulusan yang mampu mandiri yang bekerja dan bersaing sebagai ahli di bidangnya masing-masing sesuai dengan diduduki selama penelitian. Siswa lulusan SMK yang independen wiraswasta akan mampu bersaing di era global. Lulusan akan dipengaruhi oleh kondisi pembelajaran kewirausahaan di sekolah bekerjasama dengan bisnis (industri) mempelajari proses pembelajaran. Pendidikan kejuruan industri yang mempersiapkan seseorang untuk lebih mampu bekerja dalam kelompok kerja atau lapangan kerja dari pekerjaan yang sother a. Di SMK N 3 Kudus lembaga pendidikan yang mempersiapkan siswa untuk dapat bekerja secara mandiri dalam bidang tertentu. Dunia Business School dan pelaksanaan pendidikan memiliki peran penting dalam pengembangan pendidikan dalam hal ini diimplementasikan dalam proses pembelajaran. Berdasarkan latar belakang tersebut, maka dapat diambil untuk fokus masalah sebagai berikut: Proses pembelajaran kewirausahaan oleh siswa SMK N 3 Kudus di kelas, praktek dan belajar di dunia usaha untuk siswa kapal pengusaha di SMK N 3 Kudus, Dunia kerja sama antara sekolah dan bisnis (Dunia industri) dalam kewirausahaan mengajar untuk siswa di SMK N 3 Kudus dan dampaknya terhadap pembelajaran kewirausahaan siswa melalui kolaborasi antara sekolah dan bisnis (industri) pengetahuan (keterampilan) kompetensi siswa kewirausahaan di SMK N 3 Kudus. Dari hasil analisis dapat disimpulkan bahwa dampak dari kolaborasi antara Dunia Sekolah Bisnis dalam pembelajaran kewirausahaan pada siswa SMKN 3 Kudus mampu mengembangkan jiwa kewirausahaan siswa sehingga dapat meningkatkan semangat kemandirian siswa dalam pekerjaan. Sebagai akhir dari deskripsi penelitian, penulis memberikan saran sebagai berikut: untuk staf pengajar di sekolah-sekolah menengah kejuruan, keterlibatan dalam pembelajaran masing-masing harus bisa memasukkan materi yang berkaitan dengan kewirausahaan sebagai subjek merupakan bagian dari pembelajaran proses siswa untuk dapat memberikan dorongan untuk berwirausaha secara mandiri. Sekolah dan bisnis merupakan entitas tunggal dalam proses pembelajaran di sekolah menengah kejuruan maka kedua lembaga harus saling mendukung untuk keberhasilan program pendidikan dan pelatihan yang telah digariskan dalam UUD 1945 pembukaan mencerdaskan kehidupan bangsa dan seluruh tumpah darah . Kata kunci: Enterpreunership itu, Sekolah, Usaha Dunia (Industrial Dunia)